Intellectual property and blockchain technologies for the implementation of crisis European and state operations - Turakulova Nazira Abdushukur kizi (Genius Journals, 2023)
Ensuring the protection of intellectual property and increasing the level of its protection on a global scale are important guarantees of economic development and increasing the investment attractiveness of the country, blockchain technologies are one of the digital technologies aimed at ensuring these trends. In the article, the author separately studied the role of blockchain technology in the effective protection of data of intellectual property rights and properly analyzed the significance of this digital technology. Directly in the field of intellectual property, the protection of copyright and related rights, which are among the main institutions of intellectual property law, is violated by third parties, and the article talks about the role of this technology in ensuring the protection of this institution. The features of the blockchain as a way of functioning the technology, its technical significance, the guarantee of the property rights of the copyright holder are studied.
Keywords: intellectual property; copyright; cryptocurrency; blockchain